2023
DOI: 10.1002/adfm.202212231
|View full text |Cite
|
Sign up to set email alerts
|

Fast Expandable Chitosan‐Fibers Cryogel from Ambient Drying for Noncompressible Bleeding Control and In Situ Tissue Regeneration

Abstract: Hemorrhage control, especially noncompressible wound hemostasis, is a tremendous challenge in military injuries and other traumas worldwide. Here, a cryogelation strategy and subsequent solvent exchange are developed for the hydrogen bond-induced self-assembly of chitosan fibers and the production of fast expandable chitosan cryogel. Importantly, the ambient drying process facilitates the repeatable deformation performance of the shape-memory cryogel with a response time of ≈1.7 s. Due to the capillary-like st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Taken together, the printed structure with a 30% filling rate was more suited for use as a noncompressible hemostatic material based on its liquid absorptivity and deformability. [ 52 ] The results of anti‐fatigue cyclic compression experiments showed that after 50 compression cycles at a high strain of 60%, the CBES with a 30% filling rate virtually maintained its original volume, indicating the structural stability and effective shape recovery performance of the CBES. Moreover, the compression stress‒strain curves showed that the elastic modulus of the constructs increased with increasing CBp content (Figure 2K).…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, the printed structure with a 30% filling rate was more suited for use as a noncompressible hemostatic material based on its liquid absorptivity and deformability. [ 52 ] The results of anti‐fatigue cyclic compression experiments showed that after 50 compression cycles at a high strain of 60%, the CBES with a 30% filling rate virtually maintained its original volume, indicating the structural stability and effective shape recovery performance of the CBES. Moreover, the compression stress‒strain curves showed that the elastic modulus of the constructs increased with increasing CBp content (Figure 2K).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the absence of the cryogelation process during freezing compromises the mechanical strength of the structures, thereby restricting their applications in hemostasis. In contrast, the room temperature drying process employed by Qi et al [89] proves to be a more cost-effective and straightforward alternative, yielding a cryogel with favorable mechanical properties.…”
Section: Hydrogel Spongesmentioning
confidence: 95%
“…In contrast, the room temperature drying process employed by Qi et al. [ 89 ] proves to be a more cost‐effective and straightforward alternative, yielding a cryogel with favorable mechanical properties.…”
Section: Structural Characteristics Of Hemostatic Hydrogelsmentioning
confidence: 99%
“…Owing to the synergistic effect of microfibers and nanofibers, the obtained cryogel exhibited superior compressibility and fatigue resistance. Based on this strategy, Shi et al [137] conducted ethanol solvent exchange and shape fixation under compression treatments to develop a shapememory CS cryogel, which rapidly expanded to its original shape within 1.7 s upon contact with water. Benefited from hemostatic nature of CS, microporous structure, and rapid water-sucking capability, the cryogel exhibited excellent hemostatic properties, which was demonstrated in the rat liver defect model, rat femoral artery injury model, rabbit axillary artery and rabbit vein complete transection model.…”
Section: Self-assemblymentioning
confidence: 99%